Demonstration Project on Course Redesign and Academic Productivity. - Bentley, Peter; Coates, Hamish; Goedegebuure, Leo (Office for Learning and Teaching, 2012)
The demonstration project will assess improvements to academic productivity and student learning outcomes by employing activity based costing and course redesign in six selected subjects (courses) in two participating universities. For each selected course (subject), the first step is to use activity based costing techniques to get a sound understanding of cost drivers at the academic program level. The next step will involve course redesign, which in principle relates to disaggregation of academics' roles in terms of curriculum development, pedagogy, course delivery and assessment activities and limiting staff activities to those that can only be done by academics, replacing all other activities with technology and lower cost staff. The success of the project will be determined by improvements to academic productivity and student learning outcomes. The LH Martin Institute is primarily interested in the use of activity based cost modelling techniques for understanding cost drivers.